CHOISE OF THE EFFICIENT BUNDLING UP OF PLANT FOR WASTE OILS PURIFICATION - L. A. Nagorskiy; S. M. Oldyrev (Сельскохозяйственные машины и технологии, 2015)
Scientists of the Azov-Black Sea State Engineering Institute (Don State Agrarian University) have developed a simplified technology for waste oils processing, which consists in purification of oil from insoluble deposits, water and, partly, from oxidation products. This technology allows to purify the waste oils directly at the agricultural enterprises. Under the present conditions of agricultural production it is not defined what kind of plant (tank volume, heat power, number of purifiers) is the most preferable for different enterprises with varied amount of waste oils. However, design data of such plant (tank volume, heater power, quantity of purifiers) need to be specified that it became the most effective for various farms having different volumes of waste oils. The constructional variants differ in tank thermo-insulation, volume and shape of tank as well as the number of purifiers according to the amount of oil subjected to refinement (from 3000 to 20 000 liters). It was found out that the amount of costs for oil purification depends on the production program of the enterprise. Its increase leads to costs decline. The using of big oil tank causes present costs increase. Under the increasing of the tank volume to 1000 liters costs of 1 liter oil purification increase to about 10 percent. It was shown that the number of purifiers inside the plant construction depends on the manufacturing program: 100 liters tank plant requires one purifier at the manufacturing program under 5200 liters. It is rational to use two purifiers if the manufacturing program accounts from 5200 till 16 000 liters. The larger volume of the manufacturing program (16 000 liters and more) requires three purifiers. It has been proved that tank thermo-insulation of the oil-purifying plant leads to decreasing power inputs for waste oil refinement, but increases reduced present costs because of increase of plant manufacturing cost. The economic effect of the tank thermo-insulation usage is achieved at the manufacturing program of above 16 000 liters.